Comparative investigation of antibacterial activity of cold and hot extracts of Acacia arabica against E. coli - Biswas, Deboshree; Roymon, M G (Recent Research in Science and Technology, 2013)
Both cold and hot fruit extracts of Acacia arabica were prepared in methanol, acetone, chloroform and water and their antibacterial activity was detected against five different diarrheagenic E. coli strains by broth microdilution method. MIC of cold methanolic fruit extract was found to be 0.6 mg/ml whereas MIC of hot methanolic fruit extract was observed to be 0.12-0.15 mg/ml. MIC of cold and hot acetone extract was observed to be ranged from 1.23-3.3 mg/ml and 0.4 -1.25 mg/ml whereas MIC of cold and hot chloroform fruit extract was found to be same of 0.3 mg/ml. No antibacterial activity was observed from aqueous extract. Results revealed that hot acetone and methanolic extract were more effective over cold extracts.